1994
DOI: 10.1095/biolreprod51.4.633
|View full text |Cite
|
Sign up to set email alerts
|

Use of Low-Salt Culture Medium for in Vitro Maturation of Porcine Oocytes is Associated with Elevated Oocyte Glutathione Levels and Enhanced Male Pronuclear Formation after in Vitro Fertilization1

Abstract: The effects of sodium chloride (NaCI) in Whitten's medium on intracellular glutathione concentration and on cytoplasmic maturation, as determined by monospermic penetration and male pronuclear formation of porcine oocytes, were examined. Porcine cumulus-oocyte complexes were cultured for 20 h in BSA-free Whitten's medium containing different NaCl concentrations (44.50, 68.49, 92.40, 116.40, or 140.35 mM) and supplemented with 10% porcine follicular fluid and hormonal supplements; the complexes were then cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
74
1
3

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(87 citation statements)
references
References 40 publications
9
74
1
3
Order By: Relevance
“…With BCB+ oocytes, the difference between the percentage of cleaved embryos (45.3%) and the percentage of 2PN oocytes (39.7%) was reduced which suggests a lower number of haploid embryos obtained with BCB+ oocytes matured with cysteamine. Several authors have found an effect of intracytoplasmic GSH levels on MPN formation [15,16,28,31,33,34]. In our study we observed significantly higher percentages of MPN in oocytes matured with cysteamine compared to the control group (80.3 vs. 61.5%, respectively).…”
Section: Discussionsupporting
confidence: 58%
“…With BCB+ oocytes, the difference between the percentage of cleaved embryos (45.3%) and the percentage of 2PN oocytes (39.7%) was reduced which suggests a lower number of haploid embryos obtained with BCB+ oocytes matured with cysteamine. Several authors have found an effect of intracytoplasmic GSH levels on MPN formation [15,16,28,31,33,34]. In our study we observed significantly higher percentages of MPN in oocytes matured with cysteamine compared to the control group (80.3 vs. 61.5%, respectively).…”
Section: Discussionsupporting
confidence: 58%
“…Intracellular content of GSH was measured as described by Funahashi et al (1994). Cumulus-free oocytes were washed three times in M2.…”
Section: Assay For Intracellular Gshmentioning
confidence: 99%
“…As described in our previous report [12], the maturation medium used was BSA-free Whitten's Medium containing various concentrations (44.50, 68.49, 92.40, 116.40 and 140.35 mM) of NaCl supplemented with 10% (v/v) porcine follicular fluid and hormonal supplements (10 IU eCG/ml, 10 IU hCG/ml and 1 µg estradiol/ml). Mean osmolarity of the maturation medium containing various concentrations of NaCl (44.50, 68.49, 92.40, 116.40 and 140.35 mM) was 214.5 ± 0.7, 254.5 ± 0.5, 295.0 ± 0.4, 333.5 ± 0.7 and 373.3 ± 0.3 mOsM, respectively.…”
Section: Maturation Mediamentioning
confidence: 99%
“…Further, the histone H1 kinase activity is correlated with oocyte glutathione content which, in turn, also affects male pronuclear development [12,13]. The present studies were undertaken to determine; 1) the effects of sodium chloride concentration in maturation medium on histone H1 kinase activity at the end of in vitro maturation, and 2) the correlation of histone H1 kinase activity and oocyte glutathione content at the end of culture for maturation.…”
mentioning
confidence: 99%